2019
DOI: 10.3389/fpls.2019.01568
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Role of Seed Oil Body Proteins in Metabolism and Plant Development

Abstract: Oil bodies (OBs) are ubiquitous dynamic organelles found in plant seeds. They have attracted increasing attention recently because of their important roles in plant physiology. First, the neutral lipids stored within these organelles serve as an initial, essential source of energy and carbon for seed germination and post-germinative growth of the seedlings. Secondly, they are involved in many other cellular processes such as stress responses, lipid metabolism, organ development, and hormone signaling. The biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 133 publications
2
51
0
Order By: Relevance
“…Caleosins have been demonstrated to play critical roles in many cellular and biological processes that are coupled closely to synthesis during the mature stage or degradation of storage lipids during seed germination, lipid trafficking/turnover and structural stabilization of LDs in plants (Poxleitner et al ., 2006; Huang, 2018; Shao et al ., 2019). An endoplasmic reticulum (ER)‐localized caleosin and an LDs‐localized caleosin have been identified in the embryos of Brassica napus (Hernandez‐Pinzon et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Caleosins have been demonstrated to play critical roles in many cellular and biological processes that are coupled closely to synthesis during the mature stage or degradation of storage lipids during seed germination, lipid trafficking/turnover and structural stabilization of LDs in plants (Poxleitner et al ., 2006; Huang, 2018; Shao et al ., 2019). An endoplasmic reticulum (ER)‐localized caleosin and an LDs‐localized caleosin have been identified in the embryos of Brassica napus (Hernandez‐Pinzon et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Oil body proteins have been shown to maintain oil body integrity and protect TAG from coalescence and degradation [ 53 , 74 ], emphasizing the importance of TAG packaging/stability in oil bodies, which was thought to be rate limiting and a key determinant for oil accumulation [ 76 , 77 ]. An increasing body of evidence have indicated that oil accumulation appeared to be tightly associated with the expression levels of TAG storage genes, particularly OBO genes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LD resident protein in plants, oleosin, is proposed to comprise an N-terminal amphipathic domain, a central hydrophobic domain, and a C-terminal amphipathic a-helical domain. The central domain anchors oleosin into the hydrophobic core of LD and N- and C-terminal domains are proposed to reside on the monolayer phospholipid membrane of LDs(35, 36). Using bioinformatic tools, we analyzed the possible secondary structure of LDAMP1 (Supplemental Information).…”
Section: Discussionmentioning
confidence: 99%